Peran Dinas Sosial Dalam Pembinaan Anak Jalanan Di Kota Makassar - Wahyudi, Andi; Usman, Djailan; Mone, Ansyari (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2021)
This study purposed to determine how the role of the Social Service in fostering street children in Makassar City and to determine the supporting and inhibiting factors of the city government in handling street children in Makassar City. This study used qualitative research. Data collection techniques were observation, interview and documentation. The research informants in this study were 10 people. The results of the study showed that the aspect of prevention was carried out by patrol activities every day routinely by the Saribattang Rapid Reaction Team (TRC), the advanced coaching aspect was the activity carried out by the Makassar City Social Service for finding out the reason for children taking to the streets by way of identification or assessment in RSPA (Child Social Protection House), and aspects of rehabilitation of street children rehabilitation was the cooperation between the Makassar City Social Office and the Narcotics Abuse Group Foundation (YKP2N). Keywords: Role of Social Service, Development of Street Children